ANALISIS GAYA BELAJAR SANTRI BERPRESTASI PONDOK PESANTREN AN-NUR 2 BULULAWANG MALANG - Putri Malawangi, Rachmicha Devia; Syahri, M (Civic Education Department, Faculty of Teacher Training and Education, University of Muham, 2016)
This research was carried out because the difficult thing done by students who study at Islamic boarding schools is time, how students can divide short learning time, with a solid routine. The purpose of this study is to find out (1) the learning styles of high-achieving students in Islamic boarding schools. (2) how students deal with less effective time for learning and doing assignments. (3) Supporting factors of high-achieving students in Islamic boarding schools. This type of research is a descriptive study with research subjects are students in An-Nur Bululawang Islamic boarding school. Data was collected using interviewtest results, documentation, and observation. The results of the data obtained in the form of interviews, observation and documentation were then analyzed. Descriptively, the results of the study show: (1) that the difference in the learning of students with high achievements and underachievement of students lies in their learning motivation. Motivation and enthusiasm for high learning tend to be owned by high achieving students with good learning. (2) there isno special way students achievers are better at managing leisure time. (3) there is no specific factor students with more achievement have and instil motivation into themselves.